História da matemática: do livro didático à sala de aula - Souza, Emerson Melo de (Brasil, 2023)
This work aims to investigate the use of the History of Mathematics (HM) in mathematics teaching. This use will be observed by three main points: the HM approach in mathematics textbooks; the production of didactic support material supported by HM; and the investigation of “if” and “how” teachers use HM in their classes. To find answers to the questions in this research, the methodology of Narrative Review (RN) of the literature was used, with a qualitative approach, searching for studies published in the area. A total of 932 studies were found, of which 38 were selected to belong to the scope of the RN. Some of the results pointed out in the research were the limitations regarding the use of HM in textbooks, as the books approved by the National Textbook Plan (PNLD) give preference to a traditional approach to HM content to the detriment of using it as a didactic strategy, which, according to the researchers, this second is the best way to approach HM in textbooks. The production of didactic material with a focus on HM arises mainly from the need for didactic resources that adequately deal with HM, a need generated by the limitations of the textbook. However, the use of HM in the classroom is not a trend among teachers, despite the production of para didactic material, the textbook is still the teacher's main source of information and methodological resource, which influences the use of HM or any other content in math classes.